The dynamic structure of aesthetic experience - Polyakov, Alexey M.; Pugach, Maria V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article deals with the dynamic structure of aesthetic experience as a step-by-step comprehension of the artistic image. The sign and symbolic ways of understanding the artistic image are described. The article presents an analysis of the psychological mechanisms of identification, interpretation, resistance in the aesthetic experience of the artistic image. The dynamic structure of aesthetic experience can serve as a basis for further construction of the experimental research methodology of this process in ontogenesis. In the dynamic structure of the aesthetic experience, the following components are highlighted: the reconstruction of the objective content of the artistic image, the isolation of the artistic image, awareness of the antinomy of the artistic image, «immersion» in the artistic image, awareness of the inner position, the formation of a subjective attitude to the artistic image.